MEMANFAATKAN IRIGASI SEBAGAI SUMBER ENERGI LISTRIK MIKROHIDRO DI SINGOSAREN WUKIRSARI IMOGIRI BANTUL JOGJAKARTA - Muhammad Suyanto (JURNAL GAUNG INFORMATIKA, 2017)
The development of contemporary technology provides a variety of environmental impacts, both positive and negative. This is a logical consequence of every developm ent of life for people both in rural and urban areas, through the Tri Dharma Perguruan Tinggi, a teacher can do community service. In order for universities to deal directly with the community through the practice of science and technology, community service activities should be undertaken. Community Service Program (Abdimas) is not only done by lecturers, but also by students through Real Work Lecture (KKN). The devotion to the community who carried out taking the tofik Utilizing Irrigation As a Source of Micro hydro Energy in Singosaren Wukirsari Imogiri Bantul Jogjakarta. Along with human nature that wants to always change and dynamic, hence since the invention of electric current until now, the source of electricity become a basic requirement for human in fulfilling and supporting the necessity of life, so that electricity play a very important role in technological development and development of the present to the future. With the presence of microhydro generator in Wukirsari village will add positive impact to the community, if the night through mikrohidro can be used as a means of public street lighting so that the security and anxiety during the day is reduced and to increase the income of the village of the formation of carpentry group by utilizing the carpentry tools require electricity from microhydro.